Evaluation Of Sanitation Implementation Of Refill Drinking Water Depots In Muaro Jambi District - Arnild Augina Mekarisce; Zuli Rodhiyah; Samsidar Samsidar (International Journal Of Health Science, 2024)
Background: Evaluation of cross-sectoral control of refillable drinking water depot is a strategic role in protecting consumers to obtain standardized drinking water quality. Objective: The purpose of this study was to evaluate the factors in the control and management of refillable drinking water depot in the working area of the Muaro Jambi District Health Center. Methods: The method used was a descriptive qualitative approach, which is to understand the phenomenon of the research subject holistically. Results: The results showed that the evaluation conducted by the health office was not optimal, most of the refillable drinking water depots in the Puskesmas working area had not been inspected. This is influenced by limited human resources in monitoring and evaluating each refillable drinking water depot, lack of socialization and education to refillable drinking water depot businesses and the community regarding the importance of consuming quality-assured drinking water, and especially the lack of awareness of refillable drinking water depot businesses to pro-actively meet drinking water quality standards. Conclusion: The lack of optimal cross-sectoral control of refillable drinking water depots is influenced by human resources and socialization and education programs, along with community awareness. It is expected that there will be more intensive integration between the health center, health office, and village officials who play a role in monitoring and evaluating the management of refillable drinking water depot.